2014
DOI: 10.5306/wjco.v5.i3.495
|View full text |Cite
|
Sign up to set email alerts
|

Pattern response of dendritic cells in the tumor microenvironment and breast cancer

Abstract: Breast cancer (BC) is the most common malignant neoplasm and the cause of death by cancer among women worldwide. Its development, including malignancy grade and patient prognosis, is influenced by various mutations that occur in the tumor cell and by the immune system's status, which has a direct influence on the tumor microenvironment and, consequently, on interactions with non-tumor cells involved in the immunological response. Among the immune response cells, dendritic cells (DCs) play a key role in the ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 71 publications
0
23
0
1
Order By: Relevance
“…Moreover, tumour cells can induce direct tolerization of immune effector populations such as CTLs, DCs and NK cells through the secretion of immunosuppressive factors, including prostaglandin E2 (PGE2) and transforming growth factor beta (TGF-β) [60]. Studies have also shown that the tumour microenvironment polarizes DCs, transforming them into immunosuppressive regulatory DCs with a tolerogenic phenotype, which limits effector T cell activities, thereby supporting tumour growth and progression [56,61]. Furthermore, DC numbers and functions can be diminished in breast cancer, with low cell surface expression of CD86 and MHC II as well as low IL-12 secretion demonstrated [62].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, tumour cells can induce direct tolerization of immune effector populations such as CTLs, DCs and NK cells through the secretion of immunosuppressive factors, including prostaglandin E2 (PGE2) and transforming growth factor beta (TGF-β) [60]. Studies have also shown that the tumour microenvironment polarizes DCs, transforming them into immunosuppressive regulatory DCs with a tolerogenic phenotype, which limits effector T cell activities, thereby supporting tumour growth and progression [56,61]. Furthermore, DC numbers and functions can be diminished in breast cancer, with low cell surface expression of CD86 and MHC II as well as low IL-12 secretion demonstrated [62].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 98%
“…Unfortunately, in the context of breast cancer, tolerance towards TAAs reduces immune recognition and malignant cell clearance, thus facilitating tumour development and metastatic progression [54,55]. Furthermore, tolerance to a particular TAA can be induced via cross-presentation of the antigen by APCs unable to transmit positive co-stimulation [56]. As such, it is evident that cancer cells take advantage of the tolerogenic and immune-evasive processes to escape and evade immune-mediated destruction [51].…”
Section: Mechanisms Of Immunity Generation and Suppression In Breast mentioning
confidence: 99%
“…Dendritic cells (DC) play an important role in the induction of antitumor responses due to their ability to cross-present antigens to CD4+ and CD8+ T cells, thus activating them to attack neoplastic cells [37]. The maturation of DC depends on the local microenvironment wherein various factors influence the formation of either tolerogenic or immunosuppressive DC [37,38].…”
Section: Components Of the Microenvironment And Their Interplay With mentioning
confidence: 99%
“…The maturation of DC depends on the local microenvironment wherein various factors influence the formation of either tolerogenic or immunosuppressive DC [37,38]. Tumor-associated stroma shows an abundance of immature DC with impaired capacity to stimulate antitumor immunity [39].…”
Section: Components Of the Microenvironment And Their Interplay With mentioning
confidence: 99%
“…As professional APCs, DCs play a critical role in the induction of antitumor responses due to their ability to present antigens to T cells. 128 An effective antitumor immune response by T cells requires efficient antigen presentation by activated mature DCs. The maturation of DCs depends on the local microenvironment and is influenced by various inflammatory stimulants.…”
Section: Alarmins In Tumor Immunitymentioning
confidence: 99%